2013
DOI: 10.1111/hdi.12091
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat thickness is associated with impaired coronary flow reserve in hemodialysis patients

Abstract: Cardiovascular disease (CVD) is the main cause of mortality in hemodialysis (HD) patients. Epicardial fat tissue (EFT) is a new risk factor in CVD. The aim of this study was to evaluate the association between EFT and coronary artery flow reserve (CFR), which is an early indicator of endothelial dysfunction in coronary vessels of HD patients. We performed a cross-sectional study including 71 chronic HD patients and 65 age- and sex-matched healthy controls. Epicardial fat tissue was significantly higher in HD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The present study, revealed that epicardial fat thickness was highly significantly increased in hemodialysis group than the control group (P<0.01). Our study agrees with a recent study which demonstrated that EFT was significantly higher among HD patients compared to healthy controls [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study, revealed that epicardial fat thickness was highly significantly increased in hemodialysis group than the control group (P<0.01). Our study agrees with a recent study which demonstrated that EFT was significantly higher among HD patients compared to healthy controls [41].…”
Section: Discussionsupporting
confidence: 93%
“…Atakan et al, found that epicardial fat thickness was significantly higher among HD patients compared to healthy controls. In addition, their study was the first to demonstrate an inverse correlation between EpFT and coronary flow reserve in these patients [41].…”
Section: Introductionmentioning
confidence: 95%
“…In turn, this pro-inflammatory milieu has been linked to abnormalities in ventricular structure 30, 31 and incident HF 32 . Accordingly, pericardial and other similar fat depots have been associated with prevalent abnormalities in cardiac structure 6 , including coronary artery disease, hypertrophy, vascular stiffness, coronary vasomotor dysfunction, and diastolic function 8, 9, 18, 29, 33, 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Sade et al demonstrated a negative association between EAT and the coronary flow reserve in patients with angiographically normal coronary arteries 27) . Atakan et al also demonstrated a negative association between the EAT and the coronary flow reserve in 71 patients on chronic hemodialysis 28) . FMD measurement is also a predictor of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 91%